Erwiderung: Ex nihilo nihil fit - Georg Quaas (Wirtschaftsdienst, 2018)
In der Septemberausgabe 2017 veröffentlichte der Wirtschaftsdienst einen Aufsatz von Georg Quaas zur aktuellen Kritik an der makroökonomischen Geldtheorie. Dirk Ehnts setzt sich mit diesem Aufsatz kritisch auseinander und vertritt die Auffassung, dass auch heute noch in weiten Teilen der Lehre die Geldschöpfung falsch - und nicht vereinfacht - dargestellt wird. Im Anschluss erläutert Georg Quaas in einer Erwiderung seinen Standpunkt. – – In Wirtschaftsdienst 9/2017, Georg Quaas picks up the current discussion on monetary theory. With references to some p ublications by central banks, he shows that the textbook theory is still empirically correct but in need of a few clarifications. Dirk Ehnts argues that this position is refuted by recent reports published by - among others - the Deutsche Bundesbank. He shows that the process of money creation is still not correctly described in frequently used textbooks. Ehnts states that the money multiplier an d loanable funds theory should be discarded. Quaas replies that Ehnts ignores the rules of scientific development, especially the need for recognised and replicable statements as a precondition of falsifi cations. Furthermore, Quaas argues that Ehnts's empirical arguments are incomplete and imprecise , and the submitted theoretical argument (Keynesian identity) is not applicable to a two level monetary system.
Keywords: E51; E13; B59; 330